2021
DOI: 10.3389/fimmu.2021.669539
|View full text |Cite
|
Sign up to set email alerts
|

Global Trends in Research of Macrophages Associated With Acute Lung Injury Over Past 10 Years: A Bibliometric Analysis

Abstract: Acute lung injury (ALI) is an intractable disorder associated with macrophages. This bibliometric analysis was applied to identify the characteristics of global scientific output, the hotspots, and frontiers about macrophages in ALI over the past 10 years. We retrieved publications published from 2011 to 2020 and their recorded information from Science Citation Index Expanded (SCI-expanded) of Web of Science Core Collection (WoSCC). Bibliometrix package was used to analyze bibliometric indicators, and the VOSv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
75
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(85 citation statements)
references
References 43 publications
2
75
0
Order By: Relevance
“…The term bibliometric was coined in 1969 by Alan Pritchard ( Pritchard, 1969 ). Bibliometric analysis is a powerful tool that uses literature metrics or indicators to quantitively measure the research performance in a certain field ( Deng et al, 2020 ; Wang et al, 2021 ). CiteSpace and VOSviewer are two commonly used visualizing processing tools for bibliometric analysis ( Moral-Muñoz et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The term bibliometric was coined in 1969 by Alan Pritchard ( Pritchard, 1969 ). Bibliometric analysis is a powerful tool that uses literature metrics or indicators to quantitively measure the research performance in a certain field ( Deng et al, 2020 ; Wang et al, 2021 ). CiteSpace and VOSviewer are two commonly used visualizing processing tools for bibliometric analysis ( Moral-Muñoz et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several related documents were found in our datasets due to the attention of researchers to PD1/PDL1 expression in various kinds of cells ( Brummelman et al, 2018 ; Penter et al, 2019 ). A recent bibliometric study focused on single cell sequencing technologies and suggested its applications in immunology would be the next research hotspot ( Wang et al, 2021 ). We found that in single cell sequencing had been applied in the patients with anti-PD1/PDL1 therapy to figure out the changes of cell subsets after treatments and differences between responders and non-responders, which could contribute to predict prognosis, select suitable therapy strategy and monitor the condition of diseases ( Bassez et al, 2021 ; Gohil et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Local citation score (LCS) represents the number of times that an article has been referenced in the current dataset, therefore, a high LCS indicated the importance of the article in the field. Besides, the global citation score (GCS) was also been calculated, which is the number of times the article has been cited by all documents in the entire WoSCC database, and it covers the influence of the article on other areas ( Wang et al, 2021 ). The citation thresholds were set to identify the number of influential documents and we also concerned the citations per year since their publication to define the references with citation bursts ( Mulet-Forteza et al, 2019a ; Merigó et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…We focused on searching for articles in the WoS core collection database using comprehensive search strategy to cover more publications. In our study, search terms included “antimicrobial/antibiotic stewardship”, “antimicrobial/antibiotic management”, “antimicrobial/antibiotic management strategies”, “antimicrobial/antibiotic stewardship programme” and “surgery/surgical”, according to previous studies ( 7 , 10 , 11 ). Additionally, language was restricted to English, and document type was restricted to original articles published from January 1, 2011 to December 31, 2020.…”
Section: Methodsmentioning
confidence: 99%